Traumatic hernia associated with Morel-Lavallé lesion in closed abdominal trauma: case report - L. Lugo, Leonel; Ramírez, César I. G.; Marrufo, Laura A. De la M. (International Surgery Journal, 2025)
The traumatic hernia, is an important cause of laparotomy exploration between all the trauma cases that the trauma surgeon is get used to it. In this case we review a patient case where a traumatic hernia was associated with a morel-Lavalle lesion, these two injuries are associated with an increase in the morbidity sometimes requiring a reconstruction of the abdominal wall with multiples surgeries between, this is a review of the actual guidelines and surgery treatments emphasizing the complex panorama and the even evolving treatments with this kind of injuries.